Occurrence of hepatocellular carcinoma after direct-acting antiviral therapy for hepatitis C virus infection: literature review and risk analysis. Issue 7 (3rd July 2019) - Galati, Giovanni; Muley, Moises; Viganò, Mauro; Iavarone, Massimo; Vitale, Alessandro; Dell'Unto, Chiara; Lai, Quirino; Cabibbo, Giuseppe; Sacco, Rodolfo; Villa, Erica; Trevisani, Franco
ABSTRACT: Introduction : Concerns were raised about a high occurrence of hepatocellular carcinoma (HCC) after successful treatment of chronic hepatitis C (CHC) by direct-acting antivirals (DAAs). Areas covered : The authors summarize the clinical studies reporting the occurrence rate and risk factors of HCC after DAAs in CHC. Expert opinion : The recent introduction of all-oral DAAs has substantially changed the scenario of CHC, achieving a sustained virological response (SVR) in >90% of cases. Earlier concerns raised about an increasing incidence of HCC post-DAAs were flawed by large heterogeneity of patients, the limited number of well-designed prospective studies (only nine, up to date) and the inclusion of a large number of patients with advanced liver disease, previously excluded from interferon-based studies. Current data on DAAs have shown a lower risk of HCC development; however, they were unable to identify patients at greater risk for HCC occurrence after SVR. Surveillance strategy, likely lifelong, is mandatory in these patients according to general expert opinion.